Transisi Paradigmatik Korporasi dan Konstruksi Pertanggung Jawaban Kejahatan Korporasi Era Globalisasi - Fajar Dian Aryani (Kosmik Hukum, 2021)
Globalization cannot be separated from corporations. The development of the corporation through its products has been able to "bewitch" various areas of people's lives, and even the development of the corporation has also given birth to new forms of crime, namely corporate crime. To the development of corporate crime, national law has responded by harmonizing the subject of criminal law. As a result, corporations are included as subjects of criminal law whose arrangements are contained in legislation outside the Criminal Code. Construction of corporate criminal responsibility in legislation outside the Criminal Code, namely the maker can be convicted if he has committed a criminal act as formulated in the law, regardless of how his inner attitude (strict liability) and the imposition of responsibility on someone for actions committed by people other, solely based on the relationship between the two people (vicarious liability). The construction of criminal liability in the statutory provisions governing criminal liability, there are provisions that apply only the strict liability doctrinal approach and the vicarious liability doctrinal approach, and/or apply both.Keywords: Corporation, strict liability, vicarious liability